LEADERSHIP MANAGEMENT OF SCHOOL PRINCIPLES: A Case Study of Public Elementary Schools in Bogor Regency - Nindie, Ayu (Perhimpunan Sarjana Ekonomi dan Bisnis, 2022)
In the context of the organization, the leader has an important role in moving all members to achieve goals. Likewise in educational institutions, principals are the main actors of success, so there needs to be a standard of leadership management. Principal leadership management standards can help strengthen the management function, so that all parties involved can maximize their roles and functions. In fact, this research was conducted to examine the principal's leadership management function through a qualitative approach. In the process of disclosing information, descriptive analysis technique is used, in which the basic explanation is based on data and information obtained from correspondents. The research informants were the principals of public schools in Bogor district, precisely in Parung sub-district. Research data obtained through interviews and observation. The results of the study indicate that in general all school principals have carried out their functions in accordance with applicable regulations, although their implementation has not been optimal or varied. In practice, leadership management is highly dependent on the personality and background of each principal. There are some principals who are dominant in the planning aspect, but the organization, task execution, and control are ordinary. So did the other principals.